Les Heu, une famille patricienne de Metz au Moyen-Age (XIVe-XVIe siècle) - Mercier, Pierre-Marie (Université de Metz, 2011)
The study proposed on the family of Heu consists of three parts. The first one is a reconstruction of the family of Heu generation after generation since their arrived in Metz until XVIth century, is on about three centuries. The second part reconstitutes not only the land heritage of Heu but it also brings to light the mechanisms which underlie the constitution of these heritages. The chapters which compose this economic part, show how the system of the "engagère" allows the transfer of the real estates held/detained by a minor nobility forced by the difficulties towards the financiers of Metz. Finally, the third part of the report concerns the implication of Heu in the society. More particularly, this section aims at showing in a concrete and argued way how a family "foreigner" reaches, within two generations, to become some of the most important families of Metz and to take a rank among the urban patriciat. This thesis brings to light the big features of the history of Heu: a family of new men becomes in the first half of the XVIth century the richest property owners of Metz, a fortune which remains until XVIth century; they reach by marriages in the middle of the noble patriciat. But they do not seem to play a leading role among the leaders of the city until XVIth century and are little interested in the ecclesiastical life safe in the first half of the XVIth century when the family operates a complete reversal in its participation in the public and religious life
Keywords: Geschichte 1300-1600; Rôle de Ban; Paraige; Généalogie; Metz; Les heu; Famille / France / Metz (Moselle) / Moyen âge / Thèses et écrits académiques; Adelsfamilie; Frankreich; Hochschulschrift